2008
DOI: 10.1103/physreva.78.052321
|View full text |Cite
|
Sign up to set email alerts
|

Generating entanglement between quantum dots with different resonant frequencies based on dipole-induced transparency

Abstract: We describe a method for generating entanglement between two spatially separated dipoles coupled to optical micro-cavities. The protocol works even when the dipoles have different resonant frequencies and radiative lifetimes. This method is particularly important for solid-state emitters, such as quantum dots, which suffer from large inhomogeneous broadening. We show that high fidelities can be obtained over a large dipole detuning range without significant loss of efficiency.We analyze the impact of higher or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Using the linearization of the Heisenberg-Langevin equations, a type of dipole-induced transparency (DIT) can be well described [31,32], which is an analog of electromagnetically induced transparency (EIT) in atomic system [36][37][38][39]. Such a procedure by ignoring these nonlinear terms has been commonly adopted in many previous studies [40][41][42][43][44][45][46][47][48][49]. In the present work, we take into account the bichromatic driving field consisting of a cw control field and a cw probe field as well as the strong-coupling condition.…”
Section: Numerical Results and Discussion About High-order Sidementioning
confidence: 99%
“…Using the linearization of the Heisenberg-Langevin equations, a type of dipole-induced transparency (DIT) can be well described [31,32], which is an analog of electromagnetically induced transparency (EIT) in atomic system [36][37][38][39]. Such a procedure by ignoring these nonlinear terms has been commonly adopted in many previous studies [40][41][42][43][44][45][46][47][48][49]. In the present work, we take into account the bichromatic driving field consisting of a cw control field and a cw probe field as well as the strong-coupling condition.…”
Section: Numerical Results and Discussion About High-order Sidementioning
confidence: 99%
“…Entangling quantum dot spin with a flying photon could enable photon mediated entanglement between spatially separated quantum dot spin qubits [14,92] as well as other matter qubits [93] for creating hybrid quantum systems. These capabilities could ultimately lead to realization of long distance quantum networks [1,2] and distributive quantum computation [3].…”
Section: Discussionmentioning
confidence: 99%
“…All of our calculations so far assumed that the atom and cavity-QD system are driven with sufficiently weak excitation such that σ z → −1, where σ z is the population inversion operator. For the QD, it has been previously shown that the weak emission lifetime of the QD [11]. For any N ref one can in principle satisfy weak excitation by make τ p sufficiently long.…”
Section: Validity Of Weak Excitation Limitmentioning
confidence: 99%
“…Photon mediated entanglement has been proposed for entangling like systems such as atoms [6,8], NV centers in diamond [9], and cavity-coupled QDs [10,11]. It has been experimentally demonstrated between electrostatically trapped ions [12] and atomic ensembles [13][14][15].…”
Section: Introductionmentioning
confidence: 99%